EVALUASI KEBIJAKAN DISTRIBUSI PROGRAM BERAS SEJAHTERA DI DESA TOLOK 1 KECAMATAN TOMPASO KABUPATEN MINAHASA - WOWILING, VANDA; POSUMAH, JOHNNY HANNY; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2018)
abstract: Rastra program is one of the government's strategy to eradicate poverty, especially in fulfilling the need of food for poor people which aims to help reduce the burden of Poor Household in fulfilling basic food needs as one of the basic rights of society. But in the implementation of this program often experience various problems, rastra not until channeled into the hands of RTS-PM rastra, not right target, not appropriate price, not timely, not appropriate quality. It is therefore necessary to evaluate the implementation of the program to see if the implementation has been done successfully in accordance with the general guidelines as appropriate. Program evaluation is to measure program's achievement, that is measure the effect of a program on the goals to be achieved and determine the success rate of the program of the activities made and to contribute the thinking to the decision maker about a program to improve the program to come. Based on the results of the research, the achievement of the indicator according to William Dunn is the effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy as a measure of successful implementation on the performance of the program, indicating that the implementation of distribution of Rastra Program Year 2017 in Tolok 1 Village is still not running maximally. Keyword : Evaluation, Policy, Distribution, Prosperous Rice